2022
DOI: 10.1037/cou0000593
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy session frequency: A naturalistic examination in a university counseling center.

Abstract: With increasing demand for psychotherapy services, clinicians are carrying increasingly large caseloads (Bailey et al., 2020). As the number of new intakes exceeds the number of clinical hours available each week in some settings, psychotherapy is delivered on an attenuated schedule for returning clients (rather than the traditional weekly frequency); there is, however, little support for the efficacy of this practice. The present study explored the effect of session frequency on psychotherapy outcomes using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Specific adaptations needed to achieve this included a waitlist, session limits, and the innovation of a one-time consultation (Quick Care) to ensure access to the system, including when clients needed to wait for initial consultations. The Erekson et al study (2021) used between-group comparison, splitting the center into two clinics to compare the adapted service delivery model with treatment as usual. By comparing evidence from before and after Erekson et al, the present study found evidence to support the effectiveness of implementing the model over the entire center over an extended period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specific adaptations needed to achieve this included a waitlist, session limits, and the innovation of a one-time consultation (Quick Care) to ensure access to the system, including when clients needed to wait for initial consultations. The Erekson et al study (2021) used between-group comparison, splitting the center into two clinics to compare the adapted service delivery model with treatment as usual. By comparing evidence from before and after Erekson et al, the present study found evidence to support the effectiveness of implementing the model over the entire center over an extended period.…”
Section: Discussionmentioning
confidence: 99%
“…Adapting a service delivery model to the ever-increasing demand for services has been shown to be effective (Erekson et al, 2021). As described in our introduction, we adapted an existing stepped care model (Stepped Care 2.0; Cornish et al, 2017) to our purposes (Adapted Stepped Care, or ASC), including making several steps of care available and encouraging clinicians to focus on treatment planning and lower-intensity tracks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, nationally there is a trend of UCCs transitioning to what is known as stepped care models (Bailey et al, 2021;LeViness et al, 2018), which have been shown to be effective at getting students more rapid access to a variety of mental health care supports (Erekson et al, 2021;Reetz et al, 2014). A stepped care approach to mental health services recognizes that traditional 50-minute, weekly therapy appointments are the most resource intensive offering at UCCs (LeViness et al, 2018); thus, the stepped care literature stresses that not all students seeking services require weekly, 50-minute therapy appointments to address their needs (Bailey et al, 2021).…”
Section: University Counseling Centers (Uccs)mentioning
confidence: 99%